2021
DOI: 10.3390/ijerph182312779
|View full text |Cite
|
Sign up to set email alerts
|

How Does Office Design Support Employees’ Health? A Case Study on the Relationships among Employees’ Perceptions of the Office Environment, Their Sense of Coherence and Office Design

Abstract: This study investigated the current design circumstances of an office as well as employees’ perceptions of the office environment in relation to their perceived health, drawing on sense of coherence theory (comprehensibility, manageability, and meaningfulness). Previous studies have related the physical office environment to employee health. However, most studies have focused on alleviating negative effects, while health-promoting potential, including employee sense of coherence, has been overlooked. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Thus, improving the quality of hospital public spaces seems to have the potential to foster SOC in health-care environments. These findings confirm other research results and provide empirical support for the importance of design features in users’ SOC, as called for by Forooraghi et al (2021, 2022) and Williams et al (2022). The results of the present study showed that SOC improves when environmental properties increase in public spaces.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, improving the quality of hospital public spaces seems to have the potential to foster SOC in health-care environments. These findings confirm other research results and provide empirical support for the importance of design features in users’ SOC, as called for by Forooraghi et al (2021, 2022) and Williams et al (2022). The results of the present study showed that SOC improves when environmental properties increase in public spaces.…”
Section: Resultssupporting
confidence: 91%
“…The most significant aspects of comprehensibility in health-care environments are related to the patient’s experiences, such as wayfinding, legibility and clarity. Meaningfulness emphasizes social interactions and communications (Roskams and Haynes, 2019, p. 5; Forooraghi et al , 2021). Table 3 demonstrates the SOC aspects and environmental properties of public spaces related to these components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of or limited adequate storage was frequently noted as an issue – supporting the findings of past studies. Forooraghi et al (2021) found that adequate storage space is essential to managing one’s work. Specifically, workers want storage options at their desks and dedicated storage space for large items.…”
Section: Discussionmentioning
confidence: 99%
“…There were recurring comments on limited leg movement as desks were too small or fixed. Providing high-quality and adjustable furniture is essential to work management (Forooraghi et al , 2021) and beneficial to workers’ health and well-being. For example, past studies have shown the relationship between the type of furniture workers use and musculoskeletal (Karakolis and Callaghan, 2014; Robertson et al , 2013) and stimulating physical activity or reduced sitting time (Carr et al , 2016; Graves et al , 2015).…”
Section: Discussionmentioning
confidence: 99%